A Synbiotic Combination of Lactobacillus gasseri 505 and Cudrania tricuspidata Leaf Extract Prevents Stress-Induced Testicular Dysfunction in Mice - Joung, Jae Yeon; Lim, Whasun; Seo, Yeon Jeong; Ham, Jiyeon; Oh, Nam Su; Kim, Sae Hun (Frontiers in Endocrinology, 2022)
This study investigated the effects of a synbiotic combination (Syn) of Lactobacillus gasseri 505 (505) and Cudrania tricuspidata leaf extract (CT) on the hypothalamic-pituitary-gonadal axis in mice under chronic stress. Unpredictable chronic mild stress (UCMS) significantly decreased the serum levels of corticosterone, however, treatment with Syn suppressed UCMS-induced decreases. Histopathological analysis of the testes showed that these organs experienced some damage during UCMS, but this was repaired following treatment with Syn. Similarly, the transcription levels of gonadotropin-releasing hormone (GnRH), GnRH receptor, and gonadotropins, moreover, testicular development (i.e., Adam5, Adam29, and Spam1) - and steroidogenesis (i.e., Lhr, Egfr, and StAR) -related genes were significantly downregulated by UCMS. These UCMS-induced changes were inhibited by the administration of Syn, which was confirmed by the results of in situ hybridization analysis. These results suggest that the administration of Syn could attenuate the testicular dysfunctions induced by UCMS.